Right Iliofemoral Venous Thrombosis in a Prothrombin 20210GA carrier with Duplicated Inferior Vena Cava. An Unusual Case Report - Konstantinos Tigkiropoulos; Emmanouil Papadakis; Ioannis Lazaridis; Nikolaos Saratzis (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
Venous thromboembolism, presenting as deep vein thrombosis (DVT) is a disease affected by aging, with a low rate of about 1 per 10,000 annually before the fourth decade of life, rising rapidly after age 45 years, and approaching 5-6 per 1000 annually by age 80. We present the case of a 69-years old woman who presented to our emergency department with unilateral lower limb pain and swelling. Subsequent imaging revealed a right iliofemoral deep vein thrombosis, with associated duplication of her inferior vena cava. Thrombophilic screening revealed a prothrombin 20210A gene mutation. She was treated conservatively with Low Molecular Weight Heparin (LMWH) and elastic stockings.